(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
In September 2022, a ministerial decree caused a stir in Hungary. The decree in question was intended to require doctors to have the woman listen to the vital signs of the foetus (or embryo) before signing the medical records required to apply for the termination of the pregnancy. The influence of the Dobbs ruling, published by the US Supreme Court two months earlier, comes inevitably to mind. This short note offers a context to and a reflection on this development in Hungary.